Intra-ring compression strength of low density hardwoods - Zink-Sharp, Audrey; Price, Carlile (Maderas. Ciencia y Tecnología, 2025)
Engineered wood composites are being crafted with increasingly smaller and smaller components, yet a search of the literature indicates a lack of intra-ring mechanical property data for almost all commercial wood types, particularly the underutilized low density hardwoods. In addition, there is no universally accepted testing regime for determining micromechanical properties of wood samples. As a result, we developed a testing system for determining compression, tension, and bending properties of growth ring regions of wood samples. Our microtesting system consists of a 45.4 kg load stage, motor drive, data acquisition system, motor control, load cell, strain transducer, and software. In this study, intra-ring compression strength parallel to the grain was determined for small samples (a few ml3 in volume) of sweetgum (Liquidambar styraciflua), yellow-poplar (Liriodendron tulipifera), and red maple (Acer rubrum). It was determined that compression strength is weakly correlated with specific gravity but unrelated to growth rate. Specific gravity was also unrelated to growth rate. Sweetgum values were intermediate between yellow-poplar and red maple.